Pathogenic UNC13A variants cause a neurodevelopmental syndrome by impairing synaptic function - Asadollahi, Reza; Ahmad, Aisha; Boonsawat, Paranchai; Shahanoor Hinzen, Jasmine; Lohse, Mareike; Bouazza-Arostegui, Boris; Sun, Siqi; Utesch, Tillmann; Sommer, Jonas D.; Ilic, Dragana; Padmanarayana, Murugesh; Fischermanns, Kati; et al. (Nature Genetics, 2025)
The UNC13A gene encodes a presynaptic protein that is crucial for setting the strength and dynamics of information transfer between neurons. Here we describe a neurodevelopmental syndrome caused by germline coding or splice-site variants in UNC13A. The syndrome presents with variable degrees of developmental delay and intellectual disability, seizures of different types, tremor and dyskinetic movements and, in some cases, death in early childhood. Using assays with expression of UNC13A variants in mouse hippocampal neurons and in Caenorhabditis elegans, we identify three mechanisms of pathogenicity, including reduction in synaptic strength caused by reduced UNC13A protein expression, increased neurotransmission caused by UNC13A gain-of-function and impaired regulation of neurotransmission by second messenger signalling. Based on a strong genotype-phenotype-functional correlation, we classify three UNC13A syndrome subtypes (types A-C). We conclude that the precise regulation of neurotransmitter release by UNC13A is critical for human nervous system function.
CRIS-Team Scopus Importer:2025-11-28